Development of Digital Disaster Mitigation Map: Learning Innovations in Identifying Disaster Prone Points - Teuku Hasan Basri; Ilyas Ilyas; Nuraini Nuraini (Cahaya Ilmu Cendekia Publisher, 2025)
Purpose of the study: This research aims to develop digital-based learning media in the form of Disaster Mitigation Maps as a learning resource in identifying disaster-prone areas in Langsa City. With the increasing risk of natural disasters such as floods, landslides, tsunamis, earthquakes, forest and land fires, and thawing disasters, innovation is needed in delivering disaster mitigation information that is more interactive and easily accessible. Methodology: The research method used is Research and Development (R&D) with the ADDIE (Analysis, Design, Development, Implementation, and Evaluation) development model. Data was collected through observations, interviews, and questionnaires involving disaster experts, educators, and students as the main respondents. Main Findings: The results of the study show that the Digital Disaster Mitigation Map can improve students' understanding in identifying disaster-prone areas and mitigation measures that need to be taken. This media is also considered effective and attractive based on the results of expert validation and user trials. Novelty/Originality of this study: This study found that the Digital Disaster Mitigation Map was effective in increasing students' understanding of disaster-prone areas in Langsa City with an increase in understanding from 60% to 85%, and was considered innovative and effective by 90% of teachers compared to conventional methods.